Performance profile of Cold Storage Using R32 as Refrigerant for Traditional Fishing Boat with Photovoltaic as Energi Source - Suhengki, Suhengki; Manik, Henry Munandar; Yulianto, Muhamad; Hartulistiyoso, Edy; Sumantri, Willi (PERTETA, 2024)
This paper discusses the performance of cold storage using R32 refrigerant. R32 is one of the recommended refrigerant with the main advantage low ODP and GWP (Global Warming Potential) value of around 0 and 675. However, because of this refrigerant classified as a new refrigerant, the implementation is limited to air conditioning and heat pump. In this paper, R32 will be tested for cold storage applications. The cold storage performance will be studied about the achieved temperature, power consumption, cooling capacity and Coefficient of Performance without load. The testing was carried out in 2 ways, cold storage testing on a lab scale and direct testing on a 5 GT fishing boat. The performance results show that both tests on a lab scale and tests directly on a fishing boat without a load can reach a cold storage room temperature of -18oC. Meanwhile, the compressor power consumption supplied by photovoltaic is 0.653-0.776 kW. Based on the test results, shows that R32 has a positive possibility of being applied to cold storage.